Aplikasi Isotop δ13C dan δ18O untuk Lacak Balak Kayu Jati (Tectona grandis Linn.f.) di Jawa Application of Isotopes δ13C and δ18O for Teak Wood (Tectona grandis Linn.f.) Timber Tracking in Java - Agus Kholik; Djiono Djiono; Iskandar Z Siregar; Ulfah J Siregar; Lina Karlinasari; Tedi Yunanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2009)
Tracking the origin of Teak timber and its wood product is possible to be carried out using stable isotopes fingerprinting.  To enrich the available variation patterns, Teak woods samples were collected from nine Forest Management Units (FMUs) representing all provinces and Teak centres in Java.  Mills from all part of woods were mixed for analyses.  The mills were burned under vacuum in a reactor system at 1200oC for 2 h, the resulting clean CO2 was transferred to the mass spectrometer to determine its isotopic composition of δ13C and δ18O.  The generated data was then analysed using multivariate analysis.  The results showed that isotopes analysis grouped Teak populations in Java intoWest Java population and mixed Central-East Java population.  To consider wood as material for fingerprinting traded forest product, a refinement on method should be done.